Extracorporeal carbon dioxide removal in acute hypoxaemic respiratory failure: a systematic review, Bayesian meta-analysis and trial sequential analysis. (16th November 2022) - Millar, Jonathan E.; Boyle, Andrew J.; Drake, Thomas M.; Adams, Claire E.; Glass, Adam W.; Blackwood, Bronagh; McNamee, James J.; McAuley, Daniel F.
Purpose: To assess the safety and efficacy of extracorporeal carbon dioxide removal (ECCO2 R) versus standard care in patients with acute hypoxaemic respiratory failure (AHRF). Methods: MEDLINE, Embase and clinical trial registries were searched from 1994 to 31 December 2021. We included randomised controlled trials (RCTs) and observational studies. Pairs of reviewers independently extracted data and assessed the risk of bias. The primary outcome was mortality. Secondary outcomes included ventilator-free days, length of stay, safety and adverse events and physiological changes. As a primary analysis, we performed a meta-analysis of mortality until day 30 using a Bayesian random effects model. We then performed a trial sequential analysis of RCTs. Results: 21 studies met inclusion criteria: three RCTs, enrolling 531 patients, and 18 observational studies. In a pooled analysis of RCTs, the posterior probability of increased mortality with the use of ECCO2 R was 73% (relative risk 1.19, 95% credible interval 0.70–2.29). There was substantial heterogeneity in the reporting of safety and adverse events. However, the incidence of extra and intracranial haemorrhage was higher (relative risk 3.00, 95% credible interval 0.41–20.51) among those randomised to ECCO2 R. Current trials have accumulated 80.8% of the diversity-adjusted required information size and the lack of effect reaches futility for a 10% absolute risk reduction in mortality. Conclusions: The use of ECCO2 R in patients with AHRF is not associated with improvements in clinical outcomes. Furthermore, it is likely that further trials of ECCO2 R aiming to achieve an absolute risk reduction in mortality of ≥10% are futile. ECCO2 R for AHRF is associated with increased risk of intracranial haemorrhage, fewer ventilator-free days and increased mortality. Trials aiming to show ARR ≥10% are probably futile. Use is not recommended except in clinical trials or highly selected cases. https://bit.ly/3eyYRPO